Epidemiology of Biofilm Producing Acinetobacter baumannii Nosocomial Isolates from a Tertiary Care Hospital in Egypt: A Cross-Sectional Study - Asaad AM; Ansari S; Ajlan SE; Awad SM (Infection and Drug Resistance, 2021)
Ahmed Morad Asaad,1 Shamshul Ansari,2 Soma Elsayed Ajlan,3 Samah Mohammed Awad4 1Department of Medical Microbiology and Immunology, Faculty of Medicine, Zagazig University, Zagazig, Egypt; 2Department of Microbiology and Immunology, Chitwan Medical College School of Medicine, Bharatpur, 44200, Nepal; 3Department of Medical Microbiology and Immunology, Faculty of Medicine, Menoufia University, Menoufia, Egypt; 4Department of Clinical Microbiology and Immunology, Molecular Microbiology in Liver and GIT, National Liver Institute, Menoufia, EgyptCorrespondence: Shamshul AnsariDepartment of Microbiology, Chitwan Medical College School of Medicine, Bharatpur, 44200, Chitwan, NepalTel +977-9840656933Email shamshulansari483@yahoo.comObjective: This cross-sectional study aims to determine the prevalence and associated risk factors of biofilm-producing A. baumannii nosocomial isolates from a tertiary care hospital, as well as to investigate any possible association of biofilm formation with the distribution of biofilm-related genotypes and antibiotic resistance phenotypes.Methods: A total of 94 non-duplicate A. baumannii nosocomial isolates were identified, their biofilm formation was quantitatively detected using the modified microtiter plate assay, and their susceptibilities to different antibiotics were determined using the breakpoint method. Isolates were then subjected to PCR assays targeting bap, ompA and blaPER-1 genes.Results: The majority (70.1%) of isolates were biofilm producers. The most prevalent biofilm gene was ompA (63.8%), followed by bap (13.8%) and blaPER-1 (10.6%). The presence of multi- and extensive-drug resistance (MDR and XDR) was significantly associated with biofilm producers (p = 0.017 and 0.002, respectively). The length of hospital stay (aOR= 0.023), the presence of ompA gene (aOR = 0.286) or bap gene (aOR = 0.346), ampicillin/sulbactam resistance (aOR = 1), and the presence of MDR (aOR = − 0.329) or XDR (aOR = − 0.252) were considered significant risk factors associated with biofilm-producing isolates.Conclusion: The high prevalence of biofilm-producing MDR and XDR nosocomial isolates in this study is worrisome and alarming. Characterization of risk factors could help control the continuous selection and transfer of this serious A. baumannii phenotype inside hospitals and improve the quality of patients’ care.Keywords: Acinetobacter, biofilm, MDR, XDR, nosocomial infection